Optimization of process parameters for bioproduction, isolation and purification of 4-Ipomeanol from cell suspension cultures of Ipomoea batatas (L.) Lam - Mohanraj, Remya; Subha, S (Indian journal of experimental biology, 2017)
The secondary metabolite, 4-Ipomeanol from Sweet potato (Ipomoea batatas) is a potential chemotherapeutic agent for cancer. This study presents an efficient protocol for bioproduction of 4-ipomeanol, in large quantities without disturbing the natural biodiversity of I. batatas. Friable Calli from the root tubers of I. batatas were used to establish cell suspension cultures in liquid media under agitated conditions and the growth and production kinetics of the same were monitored. The presence of 4-ipomeanol was confirmed by NMR and IR spectroscopy and quantification was done using HPLC. A maximum of 7.39 mg g-1 of 4-ipomeanol was obtained under biotic elicitation of the cell suspension cultures. The elicitors were studied for optimization of the day of addition and maximum bioproduction of 4-ipomeanol was observed when elicitors were added to 4 day old suspension cultures. Further, the 4-ipomeanol thus produced demonstrated cytotoxicity against renal carcinoma cell lines.